2006
DOI: 10.1038/sj.bjp.0706839
|View full text |Cite
|
Sign up to set email alerts
|

Donitriptan, but not sumatriptan, inhibits capsaicin‐induced canine external carotid vasodilatation via 5‐HT1B rather than 5‐HT1D receptors

Abstract: Background and purpose: It has been suggested that during a migraine attack capsaicin-sensitive trigeminal sensory nerves release calcitonin gene-related peptide (CGRP), resulting in cranial vasodilatation and central nociception; hence, trigeminal inhibition may prevent this vasodilatation and abort migraine headache. This study investigated the effects of the agonists sumatriptan (5-HT 1B/1D water-soluble), donitriptan (5-HT 1B/1D lipid-soluble), PNU-142633 (5-HT 1D water-soluble) and PNU-109291 (5-HT 1D lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 37 publications
4
11
0
Order By: Relevance
“…The anti-migraine properties of triptans may be due to vasoconstriction of the carotid arterial bed via 5-HT 1B receptors and the inhibition of CGRP release from trigeminal nerves via 5-HT 1B/D receptors, in our study sumatriptan forms were inactive in the capsaicin test. This lack of efficacy of sumatriptan in this test is, at least to some degree, in line with the results obtained by other authors who have shown that intravenous sumatriptan is not effective in the inhibition of capsaicin-induced responses related to cranial vasodilatation and central nociception 53 .…”
Section: Discussionsupporting
confidence: 91%
“…The anti-migraine properties of triptans may be due to vasoconstriction of the carotid arterial bed via 5-HT 1B receptors and the inhibition of CGRP release from trigeminal nerves via 5-HT 1B/D receptors, in our study sumatriptan forms were inactive in the capsaicin test. This lack of efficacy of sumatriptan in this test is, at least to some degree, in line with the results obtained by other authors who have shown that intravenous sumatriptan is not effective in the inhibition of capsaicin-induced responses related to cranial vasodilatation and central nociception 53 .…”
Section: Discussionsupporting
confidence: 91%
“…One-minute intracarotid continuous infusions of capsaicin, α-CGRP and acetylcholine induced dose-dependent increases in the external carotid blood flow (see Figures 2 and 3; control responses) without significant changes in mean blood pressure or heart rate (not shown), as previously reported (13,14,31). These vasodilator responses to capsaicin and α-CGRP were longer lasting (between five and 20 minutes) than those to acetylcholine (between one and five minutes).…”
Section: Resultssupporting
confidence: 86%
“…After a stable haemodynamic condition for at least 60 minutes, baseline values of MAP, heart rate and external carotid blood flow were determined. Subsequently, all animals ( n = 48) received an intracarotid continuous infusion of phenylephrine (1.5 µg/min) to obtain a sustained carotid vasoconstriction, as previously reported (13,14). Twenty minutes later, all the different treatments were given without interrupting the infusion of phenylephrine.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, sumatriptan, via the activation of 5‐HT 1D , rather than 5‐HT 1B , receptors has been shown to reduce glutamate release onto SG neurons of the Vc (Jennings et al ., 2004). Although these previous studies suggest that 5‐HT 1B receptors are not involved in the anti‐migraine action of triptans in trigeminovascular sensory neurons, recent studies have suggested that a central trigeminal action of triptans, which is mediated by 5‐HT 1B rather than 5‐HT 1D receptors could be involved in the processing of craniovascular pain (Muñoz‐Islas et al ., 2006; 2009). Further studies are needed to verify whether 5‐HT 1B receptors can inhibit glutamate release from trigeminovascular afferents onto Vc neurons.…”
Section: Discussionmentioning
confidence: 99%